2016
DOI: 10.1016/j.cemconcomp.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of leaching on the local mechanical properties of an aggregate-cement paste composite

Abstract: This paper presents an experimental study to characterize the mechanical behaviour, at the local scale, of sound and degraded concrete after leaching. An experimental protocol was developed to study the effects of the calcium leaching mechanism at the interfacial transition zone (ITZ) on the mechanical properties of the cement-aggregate interface and bulk paste of model material. The process of lixiviation with deionised water occurs very slowly. The experimental study in the laboratory was accelerated by repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…Rao and Prasad [5] and Guo et al [5] found that the tensile strength of the interface between aggregate and mortar was about one third to half of the tensile strength of the mortar. Mielniczuk et al [14] and Jebli et al [7] have characterized the behavior of composites with spherical aggregate by direct compression and tensile tests. They showed that the proposed models on the macroscopic scale by Eurocode 2 to predict the behavior at rupture, are verified at the local scale considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Rao and Prasad [5] and Guo et al [5] found that the tensile strength of the interface between aggregate and mortar was about one third to half of the tensile strength of the mortar. Mielniczuk et al [14] and Jebli et al [7] have characterized the behavior of composites with spherical aggregate by direct compression and tensile tests. They showed that the proposed models on the macroscopic scale by Eurocode 2 to predict the behavior at rupture, are verified at the local scale considered here.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be kept in mind that it is just a model interfacial system that allows producing a bond between matrix and aggregate. In fact, the material preparation (mixing) greatly affects the formation of ITZ in concrete [14][15][16][17][18][19][20][21][22][23][24][25][26]. Pope and Jennings [26] reported that the interfacial zone of a limestone mortar is reduced in size by controlling the water-aggregate contact through a pre-coating procedure or by mixing the cement paste separately.…”
Section: Introductionmentioning
confidence: 99%
“…The nano-indentation technique, which is potentially the only one able to directly evaluate the mechanical properties of the interface, has its limitations due the great variability of the measurements [14,15]. That is why different authors have thus tried to perform tests with simplified models such as sandwiched specimens in which cement paste (or mortar) is in contact with coarse aggregate [16][17][18][19][20][21][22][23][24][25]. It has to be kept in mind that it is just a model interfacial system that allows producing a bond between matrix and aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial transition zone (ITZ) is considered an additional phase introduced by the presence of aggregates, which is characterised by higher porosity than the bulk paste and a higher concentration of portlandite, which increases calcium leaching. A protocol was developed to study the effects of the calcium‐leaching mechanism at the ITZ on the mechanical properties of the cement–aggregate interface using phthalein dyes . Furthermore, the liquid‐setting accelerators containing phthalein dyes impart colour to the cement mix until there is a hardening of the mix so that the presence/absence of the setting accelerators in the mix can be checked visually .…”
Section: Industrial Applications Of Phthalein Dyesmentioning
confidence: 99%